Drug Repurposing on Adenylosuccinate Synthetase of Plasmodium falciparum – A protein dynamics study (Journal of Pharmaceutical Negative Results, 2022)
Malaria, a deadly disease in worldwide caused by female mosquitoes bite with the help of plasmodium parasites. In the current study, the major is to gain insights on inhibition of key malaria target Plasmodium falciparum adenylosuccinate synthetase (AS) using drug repurposing strategy. Using the experimental 3D structure of AS, rational drug design was performed using specific anti-malarial drugs by computational methods. Two phase virtual screening was carried out in AutoDock Vina and Autodock and top leads quinidine and quinine were screened based on respective binding energy evaluation and weak interactions in protein-lead complex. Molecular dynamics simulations of 10 ns were performed on lead complexes for evaluating the stability and behavior of the drug binding in the dynamic system. Overall, our study will be useful in studying the structural mechanism of adenylosuccinate synthetase inhibition with anti-malarial drugs in future treatment.